Genomic Analysis of Thrombophilia Variants in the General Population for the Creation of an Effective Preoperative Screening Tool - Azar, Fadi M.; Menezes, John M. (Journal of Reconstructive Microsurgery, 2022)
Background The loss of a free flap in reconstructive microsurgery is a devastating complication in both the intraoperative and postoperative setting. Previous research has identified a variety of genetic polymorphisms that induce a hypercoagulable state and predispose patients to clot formation and subsequent free flap loss. We aim to review the risks of performing microsurgery on patients who are genetically predisposed to hypercoagulability, as well as identify options, for preoperative screening of inherited thrombophilia.Methods A thorough literature review was conducted with an online database. A total of 30 studies were reviewed to identify genetic polymorphisms that cause inherited thrombophilia. Through manual review of the literature, a table was created that included thrombotic risk factors and their associated genetic polymorphisms. If the information was available, prevalence for each thrombotic risk was also reported.Results Overall, 18 thrombotic risk factors that contribute to hereditary thrombophilia were identified and linked with specific genes and/or genetic polymorphisms. In studies that did not look at particular ethnic groups, 13 unique thrombotic risk factors were identified. In studies that examined specific ethnic groups exclusively, 12 thrombotic risk factors were identified and related to their respective gene or group of genes. Five of the 18 thrombotic risk factors identified were associated with increased risks of both venous and arterial thrombosis. The remainder of the thrombotic risk factors was associated with increased risk of venous thrombosis exclusively.Conclusion The use of genetic screening tests for hereditary thrombophilia in the preoperative setting can serve as an effective preventative measure against postoperative thrombosis. Further exploration of thrombotic risk factors and their related genetic polymorphisms are important steps in reducing postoperative free flap loss.
Keywords: genetic screening; thrombophilia; postoperative thrombosis